Schlafen4+-MDSC in Helicobacter-induced gastric metaplasia reveals role for GTPases - Ding, Lin; Sheriff, Sulaiman; Sontz, Ricky A.; Merchant, Juanita L. (Frontiers in Immunology, 2023)
MDSCs express SCHLAFEN 4 (SLFN4) in Helicobacter-infected stomachs coincident with spasmolytic polypeptide-expressing metaplasia (SPEM), a precursor of gastric cancer. To define SLFN4+ cell identity and the role of SLFN4 in myeloid cells, single-cell RNA sequencing was performed on immune cells sorted from PBMCs and stomachs prepared from uninfected and 6-month H. felis-infected mice. Slfn4 was highly induced in both monocytic and granulocytic MDSCs from infected stomachs. Both Slfn+-MDSC populations exhibited strong transcriptional signatures for type-I interferon responsive GTPases and exhibited T cell suppressor function. SLFN4-containing protein complexes immunoprecipitated from myeloid cell cultures treated with IFNα exhibited GTPase activity. Knocking down Slfn4 or PDE5/6 inhibition with sildenafil blocked IFNα induction of GTP, SLFN4 and NOS2. Moreover, IFNα induction of Slfn+-MDSC function was inhibited by inducing their reactive oxygen species (ROS) production and apoptosis through protein kinase G activation. Accordingly, in vivo disruption of Slfn4 in Gli1CreERT2 x Slfn4fl/fl mice or pharmacologic inhibition by sildenafil after Helicobacter infection also suppressed SLFN4 and NOS2, reversed T cell suppression and mitigated SPEM development. Together, SLFN4 regulates the activity of the GTPase pathway in MDSCs and precludes these cells from succumbing to the massive ROS generation when they acquire MDSC function.